Consolidated PGIS Report for Zimbabwe - Ncube, S (CGIAR Challenge Program on Water and Food, 2012)
In Zimbabwe, the Participatory Geographic Information Systems (PGIS) data collection exercise for the Challenge Program on Water and Food (CPWF‐L1) was done in three districts that fall within the confines of the Limpopo River Basin. These districts are Insiza, Matobo and Gwanda which are all found in Zimbabwe’s Matabeleland South province. In all the districts data collection was done at two levels, in which the first level entailed conducting interviews and focused group discussions with the district stakeholders. The second level of data collection entailed conducting focused group discussions with the selected communities. Three PGIS team members facilitated the data collection exercise with the support from the provincial Agritex office.